Effects of the Amount of Fly Ash Modified by Stearic Acid Compound on Mechanical Properties, Flame Retardant Ability, and Structure of the Composites - Tuan Anh Nguyen (International Journal of Chemical Engineering)
Fly ash, a waste product from thermal power plants, is one of the good alternatives for use as a filler in polymers, especially in flame retardants. Fly ash is an environmentally friendly fire retardant additive for composites, used in place of conventional flame retardant additives such as halogenated organic compounds, thus promoting environmental safety. In this study, fly ash was modified with stearic acid to improve adhesion at the polymers interface and increase compatibility. Fly ash was studied at various volumes (5, 10, and 20 wt.% fly ash) used in this study to synthesize fly ash-epoxy composites. The results show that the tensile strength, flexural strength, compressive strength, and impact strength of these synthetic materials increase when fly ash is modified to the surface, compressive strength: 197.87 MPa, flexural strength: 75.20 MPa, impact resistance: 5.77 KJ/m2, and tensile strength: 47.89 MPa. Especially, the fire retardant properties are improved at a high level, with a modified 20% fly ash content: the burning rate of 16.78 mm/min, minimum oxygen index of 23.2%, and meet the fire protection standard according to UL 94HB with a burning rate of 8.09 mm/min. Scanning electron microscopy (SEM) and infrared spectroscopy were used to analyze the morphological structure of fly ash after being modified and chemically bonded with epoxy resin background.